NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB NASHAIHUL’IBAD KARYA SYAIKH NAWAWI AL-BANTANI - Isvaro Amna Maliya; Ilyas Thohari; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Akhlaq became one's priority in societal. The decline of Akhlaq on millennials is currently one of the few due to the lack of deep religious education, which is essentially religious education has a more important role in life. The purpose of this research is to describe the values of Akhlaq education found in the book of Nashaihul'ibad by Shaykh Nawawi Al-Bantani. With the Library research method of descriptive analysis. Data derived from the book of Nashaihul 'Ibad by using techniques, collecting, quoting, checking and grouping data. Whereas in analyzing the data using the method of content Analyisys and reflective method thinking. The results of this research there are several points of education values in the book Nashailhul'ibad namely, the value of the education of Akhlaq commendable and disgraceful against Allah SWT, Akhlaq commendable and reprehensible to the Prophet Muhammad, Akhlaq commendable and disgraceful towards himself, Akhlaq commendable and disgraceful to the environment. So in other words, the result of this study has good teaching and is relevant to the current state of learners.